Uncovering the Role of Trioctylphosphine on Colloidal and Emission Stability of Sb-Alloyed Cs2NaInCl6Double Perovskite Nanocrystals - Ahmad, Razi; Zdražil, Lukáš; Kalytchuk, Sergii; Naldoni, Alberto; Rogach, Andrey L.; Schmuki, Patrik; Zboril, Radek; Kment, Štěpán (ACS Applied Materials and Interfaces, 2021)
Doping and compositional tuning of Cs2AInCl6 (A = Ag, Na) double perovskite nanocrystals (PNCs) is considered a promising strategy toward the development of light-emitting sources for applications in solution-processed optoelectronic devices. Oleic acid and oleylamine are by far the most often used surface capping ligands for PNCs. However, the undesirable desorption of these ligands due to proton-exchange reaction during isolation and purification processing results in colloidal and structural instabilities. Thus, the improvement of colloidal and optical stability of PNCs represents one of the greatest challenges in the field. Here, we report a trioctylphosphine-mediated synthesis and purification method toward Sb-alloyed Cs2NaInCl6 PNCs with excellent stability and optical features. Nuclear magnetic resonance spectroscopy enabled one to explain the role of trioctylphosphine and to reveal the reaction mechanism during crystal nucleation and growth. Under the optimized reaction conditions, in situ-generated trioctylphosphonium chloride and benzoyl trioctylphosphonium chloride serve as highly reactive halide sources, while benzoyl trioctylphosphonium and oleylammonium cations together with the oleate anion serve as surface capping ligands, which are bound strongly to the PNC surface. The tightly bound ionic pair of oleylammonium oleate and benzoyl trioctylphosphonium chloride/oleate ligands allows one to obtain monodispersed bright-blue-emitting PNCs with high photoluminescence quantum yields exceeding 50% at an optimum Sb content (0.5%), which also exhibit long-term colloidal stability. The approach based on dual cationic ligand passivation of double PNCs opens the doors for applications in other systems with a potential to achieve higher stability along with superior optical properties.
CRIS-Team Scopus Importer:2021-10-29
Keywords: cationic ligand; colloidal stability; Cs; double perovskite nanocrystals; photoluminescence